2016
DOI: 10.1097/md.0000000000004713
|View full text |Cite
|
Sign up to set email alerts
|

Single-specificity anti-Ku antibodies in an international cohort of 2140 systemic sclerosis subjects

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 59 publications
(74 reference statements)
0
27
0
3
Order By: Relevance
“…Conversely, other antibodies associated with a wide spectrum of autoimmune diseases and ILD such as anti-neutrophil cytoplasmic antibodies (ANCA) [37] and anti-Ku antibody should be considered [38,39]. Furthermore, some reports described patients with ANCA-positive interstitial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other antibodies associated with a wide spectrum of autoimmune diseases and ILD such as anti-neutrophil cytoplasmic antibodies (ANCA) [37] and anti-Ku antibody should be considered [38,39]. Furthermore, some reports described patients with ANCA-positive interstitial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to various components of this macromolecular DNA-PK complex have been reported in SLE and related SARD [84]. Although initially thought to be specific for polymyositis/SSc overlap syndrome [85], subsequent studies demonstrated that anti-Ku antibodies are also found in SLE, MCTD and SSc [86][87][88]. Additional studies revealed that anti-Ku antibodies were also detected in a variety of other SARD and were associated with polymyositis/SSc overlap syndrome in Japanese cohorts but with SLE and overlap syndromes in African-American cohorts [87].…”
Section: Dna-dependent Protein Kinase (Dna-pk/ku)mentioning
confidence: 99%
“…Myositis and arthritis combined with interstitial lung disease are the most prominent features of patients with this type of antibodies [46]. Moreover, it was found that individuals with anti-Ku are more likely to have a history of malignancy at the time of SSc diagnosis compared with anti-Ku-negative patients (27% vs. 8%) [47]. The overall increased risk was calculated as 4.6-fold higher in anti-Ku-positive patients.…”
Section: Anti-ku Antibodiesmentioning
confidence: 99%
“…The overall increased risk was calculated as 4.6-fold higher in anti-Ku-positive patients. The most commonly reported malignancies were melanoma, breast cancer and squamous cell skin cancer [47]. The link between anti-Ku antibodies and cancers might be explained by triggering autoimmunity via genetic alterations of the Ku antigen and molecular mimicry.…”
Section: Anti-ku Antibodiesmentioning
confidence: 99%